Ecological niche modelling based on the hutchinson’s three-dimensional model - Халиль, Виктория Вячеславовна; Сидоренко, Елена Сергеевна (Eastern-European Journal of Enterprise Technologies, 2014)
The notion of “ecological niche” and its parameters is analyzed in the paper. The theoretical frameworks of developing an ecological niche model for complicated conditions of technosphere (operating environment) based on the known Hutchinson’s theoretical model are considered. Basic dimensions of a geometric model are specified with regulatory requirements, standards and GOST State Standards for each of working space parameters. Selecting three limiting factors (Сi − temperature, ОС; Cd − air velocity, m/s; Cf − relative humidity, %), a mathematical model, which is presented by a parallelepiped, is worked out. The volume of the parallelepiped (or array), formed by the corresponding vectors (Сi, Cd, Cf) determines the outcome, i.e. carrying out the regulatory requirements to quality indicators (state) (O) of the ecological niche of a human being in the technosphere. The suggested approaches are substantiated by environmental minimum laws and the tolerance law, applicable to current climate parameters, defined by acceptable and optimal working conditions. The mathematical model of ecological niche allows visualizing the working space state for determining the microclimate state. A model, based on the normative values established by legislation can serve as an optimal model and a pattern for further comparing it with the model, developed on the basis of actual indicators.